Pseudoviscoelastic behavior of TiNi shape memory alloys under stress-controlled subloop loadings - Tobushi, H.; Endo, M.; Ikawa, T.; Shimada, D. (Archives of Mechanics, 2003)
The superelastic behavior of TiNi shape memory alloy under various subloop loadings were investigated. The results obtained can be summarized as follows. (1) In the case of subloop loading under strain-controlled conditions, the reloading curve passes through the unloading-start point. In the case of stress-controlled conditions, the return-point memory does not appear. (2) In the case of subloop loading under stress-controlled conditions, strain increases under constant stress in the loading process and decreases in the unloading process. (3) In the case of subloop loading under stress-controlled conditions, stress decreases under constant strain in the loading process and increases in the unloading process. (4) The above-mentioned behavior concerning the return-point memory and the pseudoviscoelastic behavior similar to creep and stress relaxation, appear according to the martensitic transformation and the reverse transformation based on the variation in stress and temperature.